PERBEDAAN KADAR GLUKOSA DARAH DALAM PLASMA NATRIUM FLUORIDA (NaF) DENGAN PENUNDAAN WAKTU PEMERIKSAAN - Apriani - apriani; Nofri Eka Yuliandi; Yaufita Lokananta (LPPM Universitas Abdurrab, 2022)
The World Health Organization (WHO) states that blood samples must be tests before 30 minutes, delaying the examination time can cause a decrease in blood glucose levels so that the results obtained cannot represent the actual state of the body. This study aims to determine whether there is a difference in NaF plasma blood glucose levels that are immediately tests without delay with those that are delayed for 4 hours. This research was conducted by experimental method using the Cobas C501 tool. Data were analyzed by statistical independent T-test. The results of the average NaF plasma blood glucose level tests without delay, delayed 1 hour, 2 hours, 3 hours and 4 hours respectively were 85.76 mg/dl, 85.40 mg/dl (percentage decrease 0.42%,), 84.96 mg/dl (percentage decrease 0.93%), 85.16 mg/dl (percentage decrease 0.70%), and 85.36 mg/dl (percentage decrease 0.47%). The results of statistical analysis concluded that there was no significant difference (p > 0.05) in the 0 – 4 hour delay in tests. So that the results of blood glucose tests on NaF plasma that were delayed for 4 hour can still be used